Blending pedagogy: equipping student teachers to foster transversal competencies in future-oriented education - Niemi, Laura H. L.; Kangas, Jonna; Köngäs, Mirja (Frontiers in Education, 2024)
Blended teaching and learning, combining online and face-to-face instruction, and shared reflection are gaining in popularity worldwide and present evolving challenges in the field of teacher training and education. There is also a growing need to focus on transversal competencies such as critical thinking and collaboration. This study is positioned at the intersection of blended education and transversal competencies in the context of a blended ECEC teacher-training program (1000+) at the University of Helsinki. Blended education is a novel approach to training teachers, and there is a desire to explore how such an approach supports the acquisition of transversal competencies and whether the associated methods offer something essential for the development of teacher training. The aim is to explore what transversal competencies this teacher-training program supports for future teachers, and how students reflect on their learning experiences. The data consist of documents from teacher-education curricula and essays from the students on the 1000+ program. They were content-analyzed from a scoping perspective. Students' experiences of studying enhanced the achievement of generic goals in teacher education, such as to develop critical and reflective thinking, interaction competence, collaboration skills, and independent and collective expertise. We highlight the importance of teacher development in preparing for education in the future during the teacher training. Emphasizing professional development, we challenge the conventional teaching paradigm by introducing a holistic approach.